1998
DOI: 10.1007/s002770050366
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem monotherapy versus combination therapy with ceftazidime and amikacin for empirical treatment of febrile neutropenic patients

Abstract: Infections remain the major cause of morbidity and mortality among neutropenic cancer patients. The current study addresses the question whether monotherapy with the new broad-spectrum carbapenem meropenem exhibits efficacy comparable to that of the standard combination therapy with ceftazidime and amikacin for empirical treatment of febrile neutropenic patients. Seventy-one patients with hematological malignancies (55%) or solid tumors (45%), neutropenia < 500/microliter, and fever > 38.5 degrees C were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 36 publications
1
14
0
2
Order By: Relevance
“…In the present study the febrile neutropenic episodes consisted of 12.8% of clinically documented infection, 30.8% microbiologically documented infections and 56.4% fever of unknown origin. This occurrence is similar to that reported by Behre et al [10] consisting of episodes in patients with and without central venous access. However in large trials, clinically defined infection was reported in 26% of the episodes [11].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study the febrile neutropenic episodes consisted of 12.8% of clinically documented infection, 30.8% microbiologically documented infections and 56.4% fever of unknown origin. This occurrence is similar to that reported by Behre et al [10] consisting of episodes in patients with and without central venous access. However in large trials, clinically defined infection was reported in 26% of the episodes [11].…”
Section: Discussionsupporting
confidence: 91%
“…We have published the algorithm used for febrile neutropenic children in our hospital [13,14]. Single-agent therapy became a possibility when broadspectrum antibiotics, such as third-and fourth-generation cephalosporins with anti-Pseudomonas activity (ceftazidime or cefepime), ureidopenicillins with ÎČ-lactamase inhibitors, and carbapenems, became available [15][16][17][18][19]. Meropenem is a carbapenem, which has a broad spectrum of antimicrobial activity [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Single agent regimens have been proven to be equivalent to combination treatment [11][12][13][14][15][16][17][18][19][20]. Th us a fi rst-line treatment with a pseudomonas aeroginosa-covering ÎČ-lactam antibiotic is recommended.…”
Section: Anti-infective Treatment Of Febrile Neutropeniamentioning
confidence: 99%